Exploring the Role of Teacher-Student Relationships in Academic Achievement: A Qualitative Study in Primary Schools - Zainullah; Moh. Mahfud; Wa Ode Riniati (Eastasouth Institute, 2023)
This qualitative research study investigates the urgent role of teacher-student relationships in academic achievement among elementary school students in West Java, Indonesia. By employing interviews, focus group discussions, observations, and parent surveys, data was collected to understand the dynamics of these relationships and their impact on academic outcomes. Thematic analysis revealed key themes, emphasizing the importance of positive teacher-student relationships, factors influencing these interactions, and their significant correlation with academic achievement. The findings underscore the urgency of prioritizing positive teacher-student relationships in educational settings to foster a supportive learning environment and enhance students' academic success.